Disease-specific differences in gene expression, mitochondrial function and mitochondria-endoplasmic reticulum interactions in iPSC-derived cerebral organoids and cortical neurons in schizophrenia and bipolar disorder - Annie Kathuria; Kara Lopez-Lengowski; Donna McPhie; Bruce M. Cohen; Rakesh Karmacharya (Discover Mental Health, 2023)
Abstract We compared transcriptomic profiles of cerebral organoids differentiated from induced pluripotent stem cells of eight schizophrenia and eight bipolar disorder patients to identify genes that were differentially expressed in cerebral organoids between two disorders. Gene ontology analysis showed relative up-regulation in schizophrenia organoids of genes related to response to cytokines, antigen binding and clathrin-coated vesicles, while showing up-regulation in bipolar disorder of genes involved in calcium binding. Gene set enrichment analysis revealed enrichment in schizophrenia of genes involved in mitochondrial and oxidative phosphorylation while showing enrichment in bipolar disorder of genes involved in long term potentiation and neuro-transporters. We compared mitochondrial function in cerebral organoids from schizophrenia and bipolar disorder subjects and found that while schizophrenia organoids showed deficits in basal oxygen consumption rate and ATP production when compared to healthy control organoids, while bipolar disorder organoids did not show these deficits. Gene ontology analyses also revealed enrichment in bipolar disorder of genes in ion binding and regulation of transport. Experiments examining the interaction between mitochondria and endoplasmic reticulum in cortical neurons from bipolar disorder subjects showed a significantly lower number of contact sites between mitochondria and endoplasmic reticulum when compared to cortical neurons from schizophrenia patients. These results point to disease-specific deficits in mitochondrial respiration in schizophrenia and in mitochondrial-endoplasmic reticulum interactions in bipolar disorder.